Correlative Organelle Microscopy: Fluorescence Guided Volume Electron Microscopy of Intracellular Processes - Loginov, Sergey V.; Fermie, Job; Fokkema, Jantina; Agronskaia, Alexandra V.; De Heus, Cilia; Blab, Gerhard A.; Klumperman, Judith; Gerritsen, Hans C.; Liv, Nalan (Frontiers in Cell and Developmental Biology, 2022)
Intracellular processes depend on a strict spatial and temporal organization of proteins and organelles. Directly linking molecular to nanoscale ultrastructural information is therefore crucial to understand cellular physiology. Volume or 3-dimensional (3D) correlative light and electron microscopy (volume-CLEM) holds unique potential to explore cellular physiology at high-resolution ultrastructural detail across cell volumes. Application of volume-CLEM is however hampered by limitations in throughput and 3D correlation efficiency. Addressing these limitations, we here describe a novel pipeline for volume-CLEM that provides high-precision (<100nm) registration between 3D fluorescence microscopy (FM) and 3D electron microscopy (EM) data sets with significantly increased throughput. Using multi-modal fiducial nanoparticles that remain fluorescent in epoxy resins and a 3D confocal fluorescence microscope integrated in a Focused Ion Beam Scanning Electron Microscope (FIB.SEM), our approach uses FM to target extremely small volumes of even single organelles for imaging in volume-EM, and obviates the need for post correlation of big 3D datasets. We extend our targeted volume-CLEM approach to include live-cell imaging, adding information on the motility of intracellular membranes selected for volume-CLEM. We demonstrate the power of our approach by targeted imaging of rare and transient contact sites between endoplasmic reticulum (ER) and lysosomes within hours rather than days. Our data suggest that extensive ER-lysosome and mitochondria-lysosome interactions restrict lysosome motility, highlighting the unique capabilities of our integrated CLEM pipeline for linking molecular dynamic data to high-resolution ultrastructural detail in 3D.